PENGARUH PEMBELAJARAN BERBASIS AI TERHADAP SIKAP KEISLAMAN DAN KETERLIBATAN MAHASISWA DALAM MATA KULIAH AL-ISLAM DAN KEMUHAMMADIYAHAN: KAJIAN KUASI-EKSPERIMENTAL - Wahab, Abdul; Syahril, Syahril; Kurnia, Kurnia; Basir B,; Jasriani, Jasriani (Journal of Innovation Research and Knowledge, 2025)
The digital transformation in higher education demanded innovation in teaching Islamic values, particularly in the Al-Islam and Kemuhammadiyahan (AIK) courses. The lack of student engagement and weak internalization of Islamic values had become major challenges in conventional AIK learning. This study aimed to examine the effect of artificial intelligence (AI)-based learning on students’ Islamic attitudes and learning engagement in AIK courses at a Muhammadiyah university. A quasi-experimental method with a non-equivalent control group design was employed, involving 60 students divided into experimental and control groups. The research instruments included questionnaires and observation rubrics, and the data were analyzed using paired sample t-tests and independent t-tests. The results showed that the experimental group experienced a significant improvement in both Islamic attitudes and learning engagement compared to the control group (p < 0.001). These findings indicated that AI-based AIK learning effectively enhanced students’ Islamic character and active participation. This study suggested the integration of contextual, value-based AI systems into AIK curriculum design in Muhammadiyah higher education institutions.